Wavelet-based identification of rotor blades in passage-through-resonance tests. (1st January 2018) - Carassale, Luigi; Marrè-Brunenghi, Michela; Patrone, Stefano
Highlights: Damping estimated in passage-through-resonance is biased due to transient response. The time-variant FRF can be estimated through the wavelet transform along an engine order line. Identification through WT and time-variant FRF is not affected by sweep velocity. Abstract: Turbine blades are critical components in turbo engines and their design process usually includes experimental tests in order to validate and/or update numerical models. These tests are generally carried out on full-scale rotors having some blades instrumented with strain gauges and usually involve a run-up or a run-down phase. The quantification of damping in these conditions is rather challenging for several reasons. In this work, we show through numerical simulations that the usual identification procedures lead to a systematic overestimation of damping due both to the finite sweep velocity, as well as to the variation of the blade natural frequencies with the rotation speed. To overcome these problems, an identification procedure based on the continuous wavelet transform is proposed and validated through numerical simulation.